(untitled) (Journal of Hama University, 2025)
There are various optimization algorithms, every one study type of optimization. Researchers are continuously designing new optimization algorithms which have less time complexity as compared to the existing algorithms. The optimization algorithms can be categorized into various types: shortest path problem, maximal flow problem, Dynamic Programming, Genetic Algorithm … . . In this paper, analysis and comparison between complexity famous optimization algorithms have been made, and the obtained results have shown that all researchers have got remarkable success in designing better algorithms, this comparison enables choose the better. For the famous applications of algorithms, this comparison comes to help researchers in choosing the better in the certain domain.